Self-Construal Priming Modulates Ensemble Perception of Multiple-Face Identities - Peng, Shenli; Zhang, Ling; Xu, Runzhou; Liu, Chang Hong; Chen, Wenfeng; Hu, Ping (Frontiers in Psychology, 2019)
This study explored the modulatory role of independent/interdependent self-construal on ensemble perception. Two experiments were conducted to study the effect of self-construal on ensemble coding of multiple-face identities (Experiment 1) and dot size (Experiment 2) separately. Before the implicit ensemble perception task, participants in both experiments were either primed with independent or interdependent self-construal via a well-validated pronoun circle task, in which they were exposed to either singular (“I,” “me,” and “my”) or plural (“We,” “us,” and “our”) pronouns in essays. The results showed that interdependent self-construal (vs. independent self-construal) featured as global processing and emphasizing interconnectedness with others enhanced the ensemble coding of high-level features (e.g., identity in Experiment 1) but not of low-level features (e.g., size in Experiment 2). To the best of our knowledge, this study was the first to investigate the role of self-construal on ensemble representations. In sum, the results of the current study supported the domain-specific mechanism of ensemble perception on one hand, and extended the effect of self-construal on single face-recognition to multiple face recognition on the other hand.